Expanding Super Edge-Magic Graphsâ - Baskoro, E. T.; Cholily, Y. M. (Journal of Mathematical and Fundamental Sciences, 2013)
For a graph G, with the vertex set V(G) and the edge set E(G) an edge-magic total labeling is a bijection f from V(G)UE(G) to the set of integers {1,2,...., |V(G)|+|E(G)} with the property that f(u) + f(v) +f(uv) = k for each uv elemen E(G) and for a fixed integer k. An edge-magic total labeling f is called super edge-magic total labeling if f(E(G)) = {|V(G)+1, |V(G)+2,....., |V(G)+E(G)|}. In this paper we construct the expanded super edge-magic total graphs from cycles C, generalized Petersen graphs and generalized prisms.